Analisis Gaya Kepemimpinan Spiritual Aṭṭhasīlanī Periode 2024 Terhadap Personal Development Di Padepokan Dhammadīpa Arāma - Linda Yassavatthi; Amita Wardhani; Uung Gondo Saputro (Jounal Nyanadassana, 2025)
This research focuses on the spiritual leadership style of Aṭṭhasīlanī and its influence on personal development. Leadership plays a strategic role in shaping the personal and spiritual growth of community members. This research employed a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The findings reveal that the spiritual leadership style of Aṭṭhasīlanī incorporates the values of vision, faith, and altruistic love. Several personal development programs such as Pālivacana training, Dhammapada recitations, and Dhamma talks have been implemented. However, the effectiveness of leadership remains suboptimal due to uneven and inconsistent program implementation. Some members still feel that their needs, especially in terms of esteem and self-actualization, have not been fully met. In conclusion, the spiritual leadership of Aṭṭhasīlanī in 2024 is considered moderately effective, but improvement is needed in execution and equal distribution of program benefits to ensure positive impacts on all members’ personal development.